Geology-geochemistry model of Betyugensk gold-antimony ore field (Republic of Sakha (Yakutia)) - Roman Gavrilov; Valeriy Voroshilov; Vladislav Senkevich; Nikolay Tyamisov; Vasiliy Shirokov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the research is caused by the necessity to improve the efficiency of revising forecast and search gold-bearing operations based on using modern methods of geochemical information processing and interpretation. The main aim of the research is to study geochemical zones and to detect abnormality of geochemical structure of Betyugenskoe gold-antimonite ore zone designating perspective areas. Research methods: calculation of statistical parameters by nonparametric statistics methods and their processing in programs: Surfer, Statistica, Corel Draw, emission spectral half-amount analyzing, analyzing in test-tube. Results. At Betyugenskoe gold ore-zones the geological-geochemical operations were performed with a view to localize gold-antimonite mineralization. The results of litho-geochemical testing by secondary dispersion haloes served as the material for charting abnormality zone of geochemical area and detection ore zones. The concentrically zoned structure of geochemical halos controlling gold-antimonite ores was determined. Zonality of abnormal geochemical field occurs in change of the following geochemical associations (from the backcourt zone to the front one): Ni, Со, Pb, Сu®Pb, B, Sn, Ni, Co®Mn, Pb, Sn, Co®Сu, Pb, Ni. The authors developed the geological-geochemical model of ore field and allocated perspective areas. Presence of geochemical associations of granite elements forming concentrically-zone structures around earlier revealed gold-antimony mineralization identifies the paragenetic bound of mineralization with untapped rock bodies of granite-diorite structure of K-P (?) age. Their outputs are mapped 6 km to the south of the search area. The analysis of geochemical information based on statistical calculations, mapping chemical elements and integrated indicators allow developing geological and geochemical model of Betyugenskoe ore field and allocating fife areas for survey and assessment work: two sections of the first stage and three sections of the second stage.